(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: Diagnosing pulmonary tuberculosis in patients without bacteriological and histopathological evidence is a challenge for physicians. Objective: Analyze some factors associated with sputum culture results in patients suspected of pulmonary tuberculosis at National Lung Hospital in 2022. Methods: A cross-sectional, descriptive study of 179 patients with suspected of having pulmonary tuberculosis at National Lung Hospital, without bacteriological evidence. Patientswere divided into two groups: A culture-positive group and a culture-negative one. Using univariate and multivariate regression techniques to identify factors associated with culture results. Results: The male-to-female ratio was 2.5 to 1. The rate of tuberculosis bacteria culture positivity in liquid medium was 56%, while 44% tested negative. Common symptoms included productive cough (53.6%); moist rales (46.9%); afternoon fever (41.9%); and chest pain (40.8%). There was no difference in risk factors for tuberculosis and suspected tuberculosis lesions on chest CT scans between culture-positive and culture-negative groups.The multivariate model included 7 independent variables: Weight loss, night sweats, hemoptysis, productive cough, smoking, history of tuberculosis, and chest CT lesions. Hemoptysis is a symptom significantly associated with positive sputum culture results. Conclusion: Consider tuberculosis treatment for patients with signs of hemoptysis, along with weight loss, night sweats, productive cough, smoking, history of tuberculosis and suspected tuberculosis lesions on chest CT scan.